Analysis of the Incidents of Bullying and Its Relation to Health-Related Quality of Life in Indonesian Adolescents - Nur Eni Lestari (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
This study aimed to analyze the incidence of bullying and its relation to health-related quality of life in Indonesian adolescents. This study used a quantitative study method with a cross-sectional approach. The sampling technique used consecutive sampling with 464 respondents in the Jakarta, Bogor, Depok, Tangerang, and Bekasi areas. The bullying instrument in this study was modified from various sources. The quality of life instrument for adolescents in this study used KIDSCREEN-27. The two instruments obtained validity test results that were greater than the R table, and the Cronbach alpha reliability test results were 0.755 and 0.759. Questionnaires were distributed via google Forms—a statistical test using chi-square. The results showed a relationship between the incidence of bullying, the status of bullying, and the type of bullying with the quality of life of adolescents (p-value < 0.001 a<0.05). What can be recommended is that special cross-sector management is needed to reduce the prevalence of bullying so that adolescents' quality of life improves.